Analisis Clustering Data Anak Balita di Posyandu Kampung Sukarame Menggunakan Algoritma K-Means - Mira Miranda; Nining Rahaningsih; Raditya Danar Dana (Jurnal Informatika dan Rekayasa Perangkat Lunak, 2024)
Nutrition has a very important role in maintaining the health of the human body, especially in children and toddlers. The current level of health of toddlers and children is still a challenge in every region. Balance in nutritional consumption has a significant impact on children's growth and development phases, increasing their learning capacity, and making a positive contribution to their future. Currently, the problem at the Mulus Rahayu posyandu Kp. Sukarame, Cileunyi Kulon Village, Bandung Regency is that there are still many parents who do not understand the importance of balanced nutrition for toddlers. Some toddlers are known to experience malnutrition problems, while others are obese. However, no attempt has been made to group data based on the nutritional value characteristics of toddlers using the K-Means Clustering algorithm, based on height, weight and age of toddlers. To categorize into groups such as good nutrition and poor nutrition. Through the application of the K-Means algorithm, it is possible to group the nutritional values of toddlers more symmetrically, providing a basis for earlier prevention efforts by posyandu cadres in handling problems of good nutrition and malnutrition. In this research, the methods applied include literature study and observation. The results of this research are able to categorize the nutritional value of toddlers as a whole, providing a basis for initial preventive steps that can be taken by posyandu cadres in dealing with good and poor nutrition of toddlers.